Attitude of the Staff Towards Farmer Producers Organization – Development and Standardization of the Scale (Indian Journal of Extension Education, 2024)
Farmer Producers Organization is an organization where the members are farmers who come together to buy inputs collectively, sell their produce in bulk eliminating the middlemen and processing the produce to gain more returns. As staff are important assets of the organization, it is advisable to measure their attitude towards the organization. An attempt was made for the construction of scale to measure the attitude of staff towards the Farmer Producers Organization using summated rating scale. After analyzing the review of literature, 48 statements were enlisted initially and were sent to 100 judges. Based on the response of 34 judges, 25 statements were finalized for item analysis. After calculating t-values, 14 statements were finalized in which 10 were positive statements and 4 were negative statements. The reliability was checked using split half method and validity was examined with the help of content validity. The reliability coefficient was found to be 0.84 which indicates that the scale is reliable.